N-glycosylation shields Phytophthora sojae apoplastic effector PsXEG1 from a specific host aspartic protease - Xia, Yeqiang; Ma, Zhenchuan; Qiu, Min; Guo, Baodian; Zhang, Qi; Jiang, Haibin; Zhang, Baiyu; Lin, Yachun; Xuan, Mingrun; Sun, Liang; Shu, Haidong; Xiao, Junhua; et al. (Proceedings of the National Academy of Sciences - PNAS, 2020)
Hosts and pathogens are engaged in a continuous evolutionary struggle for physiological dominance. A major site of this struggle is the apoplast. In Phytophthora sojae–soybean interactions, PsXEG1, a pathogen-secreted apoplastic endoglucanase, is a key focal point of this struggle, and the subject of two layers of host defense and pathogen counterdefense. Here, we show that N-glycosylation of PsXEG1 represents an additional layer of this coevolutionary struggle, protecting PsXEG1 against a host apoplastic aspartic protease, GmAP5, that specifically targets PsXEG1. This posttranslational modification also attenuated binding by the previously described host inhibitor, GmGIP1. N-glycosylation of PsXEG1 at N174 and N190 inhibited binding and degradation by GmAP5 and was essential for PsXEG1’s full virulence contribution, except in GmAP5-silenced soybeans. Silencing of GmAP5 reduced soybean resistance against WT P. sojae but not against PsXEG1 deletion strains of P. sojae. The crucial role of N-glycosylation within the three layers of defense and counterdefense centered on PsXEG1 highlight the critical importance of this conserved apoplastic effector and its posttranslationalmodification in Phytophthora-host coevolutionary conflict.